PUSAT PELATIHAN ATLET FUTSAL KABUPATEN HULU SUNGAI TENGAH - Tajri, Muhtasar; Nurfansyah, Nurfansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Futsal is the most popular sport in Hulu Sungai Tengah district, futsal its very loved sport in that region, although futsal is the most popular sport in Hulu Sungai Tengah District, in the provide of futsal facilities is inadequate. Hulu Sungai Tengah District Futsal Training Center is the area that will be the place of region futsal player to improve the quality of themselves or the team, a place that will be support development system for the region futsal player to improve their quality, to support that’s will be approach the Green Building concept on the design of Hulu Sungai Tengah District Futsal Training Center. With the Green Building approach, quality of the building users can improve so that the training performance of region futsal players increases. And the region futsal player can improve their quality, both in terms of physical, technical, and mental of region futsal players in the Hulu Sungai Tengah District Futsal Training Center.